2004
DOI: 10.1007/s00412-003-0271-3
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear bodies and compartmentalization of pre-mRNA splicing factors in higher plants

Abstract: We studied the fine structural organization of nuclear bodies in the root meristem during germination of maize and Arabidopsis thaliana using electron microscopy (EM). Cajal bodies (CBs) were observed in quiescent embryos and germinating cells in both species. The number and distribution of CBs were investigated. To characterize the nuclear splicing domains, immunofluorescence labelling with antibodies against splicing factors (U2B 00 and m3G-snRNAs) and in situ hybridisation (with U1/U6 antisense probes) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
71
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 42 publications
3
71
1
Order By: Relevance
“…Whereas speckles exhibited limited overall movements within a constrained volume, their protein components were shown to rapidly exchange with the nucleoplasmic population. Similar to previous studies on SR45 (Ali et al, 2003) and atRSp31 (Docquier et al, 2004), a subset of speckles, at any given time, was observed to merge, bud, disassemble, or assemble at new sites. However, after blocking transcription, we found that almost all of the above-mentioned dynamic events ceased, indicating that these dynamic events are also related to transcriptional activities in the plant nuclei.…”
supporting
confidence: 85%
See 4 more Smart Citations
“…Whereas speckles exhibited limited overall movements within a constrained volume, their protein components were shown to rapidly exchange with the nucleoplasmic population. Similar to previous studies on SR45 (Ali et al, 2003) and atRSp31 (Docquier et al, 2004), a subset of speckles, at any given time, was observed to merge, bud, disassemble, or assemble at new sites. However, after blocking transcription, we found that almost all of the above-mentioned dynamic events ceased, indicating that these dynamic events are also related to transcriptional activities in the plant nuclei.…”
supporting
confidence: 85%
“…Nuclear compartmentalization is thought to facilitate the regulation of transcription and pre-mRNA splicing to generate mature transcripts (Lamond and Earnshaw, 1998). However, the presence of IGCs in plant nuclei has not been previously identified (Testillano et al, 1993;Acevedo et al, 2002;Cui and Moreno Díaz de la Espina, 2003;Docquier et al, 2004). Our observations demonstrated that two SF2/ASF and one SC35-like splicing factor localize to speckles that correspond to IGCs in plant nuclei upon TEM analysis.…”
mentioning
confidence: 40%
See 3 more Smart Citations